MANHOLE MANAGEMENT SYSTEM - Sunitha, M; Amarender, K; Nayak, Dr Purushotham; Ayesha, S (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
A smart city is the future goal to have cleaner and better amenities for the society. Smart underground infrastructure is an important feature to be considered while implementing a smart city. Drainage system monitoring plays a vital role in keeping the city clean and healthy. Since manual monitoring is incompetent, this leads to slow handling of problems in drainage and consumes more time to solve. To mitigate all these issues, the system using a wireless sensor network, consisting of sensor nodes is designed. The project aims in designing a manhole management system using IOT which alerts the managing station through web page when any manhole crosses its threshold values and also the system monitor the sensors data on LCD module. This system reduces the death risk of manual scavengers who clean the underground drainage and also benefits the public. The project makes a use of water level sensor, water flow sensor, Temperature sensor, Gas sensor and raspberry pi zero w processor. The controlling device of the whole system is raspberry pi processor. In this rise in temperature, explosion due to toxic gases, overflow, manhole lid left open is detected by the sensors. The signals from the sensors are fed to the raspberry pi, which is programmed to generate alerts. In this we use sensors to detect blockage, floods, and gases. The sensors will identify the clogging inside the drainage system and will give information to the user through email and further actions will be taken care by the municipal. Nowadays, accidents due to broken and missing manhole covers are quite frequent. Manholes are not monitored properly in developing countries. These accidents can lead to serious injuries and also death. Hence, here we propose a system to overcome this problem. We have included an array of sensors for complete monitoring of the manhole cover so that such accidents can be prevented. This project includes a gas cover to monitor the gas emitted from the sewage systems so that toxicity can be monitored, the internal temperature is also monitored if a check for a change in the temperature as the property of manhole change with temperature which could need to crack formation, Also, a float sensor is used to indicate when the water level goes beyond a certain level, in case of any alert due to any of the parameters we check on the IOT website. Also, all the parameters are continuously updated on the website.